2017
DOI: 10.1051/0004-6361/201731118
|View full text |Cite
|
Sign up to set email alerts
|

Multiwavelength flaring activity of PKS 1510-089

Abstract: Aims. In this work, we analyse the multiwavelength brightness variations and flaring activity of FSRQ PKS1510-089, aiming to constrain the position of the emission sources. Methods. We report 7 mm (43 GHz) radio and R-band polarimetric observations of PKS1510-089. The radio observations were performed at the Itapetinga Radio Observatory, while the polarimetric data were obtained at the Pico dos Dias Observatory. The 7 mm observations cover the period between 2011 and 2013, while the optical polarimetric observ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 80 publications
1
22
0
Order By: Relevance
“…In this communication we discussed the monitoring campaign reported by Beaklini et al [13]. At radio wavelengths, We reported a delay between the radio and the γ-ray emission, with the high energy flux density coming first.…”
Section: Discussionmentioning
confidence: 65%
See 4 more Smart Citations
“…In this communication we discussed the monitoring campaign reported by Beaklini et al [13]. At radio wavelengths, We reported a delay between the radio and the γ-ray emission, with the high energy flux density coming first.…”
Section: Discussionmentioning
confidence: 65%
“…In Figure 2 we show the aligned γ-ray and 7 mm radio light curves, the latter was shifted by 54 days, which resulted in a good match between the maxima in both light curves. Although the different variability timescales makes it difficult to use a statistical test to confirm this delay, an analysis of the epochs of occurrence of the flares at both wavelengths by Beaklini et al [13] indicated a time delay of 54 days. The existence of delays between flares at high energies and radio wavelengths is already known in AGNs [14].…”
Section: Observation and Resultsmentioning
confidence: 99%
See 3 more Smart Citations